General practitioners' reflections on using PSA for diagnosis of prostate cancer. A qualitative study - Olav Thorsen; Eirik Viste; Torgeir Gilje Lid; Svein R. Kjosavik (Taylor & Francis Group, 2022)
Objective To investigate how GPs use the PSA test as a diagnostic tool in daily practice.Design Qualitative study using focus group interviews, the transcripts being analyzed by systemic text condensation.Subjects A total of 17 Norwegian GPs in three CME groups.Main outcome measures Exploring GPs' attitudes to national guidelines and the practical use of the PSA test.Results Detecting prostate cancer in general practice is a common and important, but difficult diagnostic issue. Our participants experienced uncertainty regarding the test when to use it, how to interpret the results and when to refer to specialist health services.Conclusion The study revealed a general ambivalence to the use of PSA. Many patients present urological problems, and many are afraid of having cancer. PSA is commonly used, but sometimes generates problems rather than solving them.Implications The use of the PSA test should be based on a thorough clinical assessment and in close collaboration with the patient.Key pointsMany patients in general practice present urological problems, and many are afraid of having cancer.GPs have a general ambivalence to the use of PSA when to use it, how to interpret the results and when to refer to specialist health services.The use of PSA sometimes generates problems rather than solving them.